2017
DOI: 10.1002/jor.23655
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of bioreactors and whole tissue cultures for the translation of new therapies to humans

Abstract: The purpose of this review is to provide a brief overview of bioreactor-based culture systems as alternatives to conventional two- and three-dimensional counterparts. The role, challenges, and future aspirations of bioreactors in the musculoskeletal field (e.g., cartilage, intervertebral disc, tendon, and bone) are discussed. Bioreactors, by recapitulating physiological processes, can be used effectively as part of the initial in vitro screening, reducing that way the number of animal required for preclinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 132 publications
0
40
0
Order By: Relevance
“…In the tendon context, various in vitro microenvironment modulators ( e.g ., mechanical stimulation, topography, stiffness, oxygen tension, media supplementation, coculture) are used to mimic the native tissue milieu, aiming to either maintain the phenotype of tenocytes (TCs) and tendon stem cells or to direct other cell types ( e.g ., dermal fibroblasts, muscle‐derived cells, bone marrow‐derived mesenchymal stem cells, adipose‐derived stem cells) toward tenogenic lineage (2327). Although physical cues, such as surface topography and mechanical stimulation, play a particularly significant role in maintaining tendon homeostasis, given the literally infinite number of permutations required to determine the optimal topographical dimensions ( e.g ., groove width, depth, and distance) (28), mechanical stimulation is favored.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the tendon context, various in vitro microenvironment modulators ( e.g ., mechanical stimulation, topography, stiffness, oxygen tension, media supplementation, coculture) are used to mimic the native tissue milieu, aiming to either maintain the phenotype of tenocytes (TCs) and tendon stem cells or to direct other cell types ( e.g ., dermal fibroblasts, muscle‐derived cells, bone marrow‐derived mesenchymal stem cells, adipose‐derived stem cells) toward tenogenic lineage (2327). Although physical cues, such as surface topography and mechanical stimulation, play a particularly significant role in maintaining tendon homeostasis, given the literally infinite number of permutations required to determine the optimal topographical dimensions ( e.g ., groove width, depth, and distance) (28), mechanical stimulation is favored.…”
mentioning
confidence: 99%
“…In the tendon context, various in vitro microenvironment modulators (e.g., mechanical stimulation, topography, stiffness, oxygen tension, media supplementation, coculture) are used to mimic the native tissue milieu, aiming to either maintain the phenotype of tenocytes (TCs) and tendon stem cells or to direct other cell types (e.g., dermal fibroblasts, muscle-derived cells, bone marrowderived mesenchymal stem cells, adipose-derived stem cells) toward tenogenic lineage (23)(24)(25)(26)(27). Although physical cues, such as surface topography and mechanical stimulation, play a particularly significant role in maintaining tendon homeostasis, given the literally infinite number ABBREVIATIONS: ACAN, aggrecan; ADF, adult dermal fibroblast; ALPP, alkaline phosphatase; BMSC, bone marrow stem cell; COL1A1, collagen type I a-1; COL10A1, collagen type X; COMP, cartilage oligomeric matrix protein; Cr, carrageenan; ECM, extracellular matrix; IBSP, integrin binding sialoprotein; MMC, macromolecular crowding; NDF, neonatal dermal fibroblast; SCXA, scleraxis; TC, tenocyte; THBS4, thrombospondin 4; TNC, tenascin-C; TNMD, tenomodulin of permutations required to determine the optimal topographical dimensions (e.g., groove width, depth, and distance) (28), mechanical stimulation is favored.…”
mentioning
confidence: 99%
“…We also believe that in the years to come electrospun scaffolds together with other in vitro microenvironment modulators will play a crucial role in the development of functional cell therapies for cartilage engineering. For example, the positive impact of bioreactors in musculoskeletal tissue engineering has been well-established (Peroglio et al, 2018) and electrospun scaffolds coupled with bioreactors have shown promise todate, even for complex structures, such as the cartilage-bone interface (Baumgartner et al, 2019). Further, considering that extracellular matrix is key modulator of cell fate through provision of biophysical, biochemical, and biological signals Watt and Huck, 2013;Kumar et al, 2017;Muncie and Weaver, 2018;Smith et al, 2018;Novoseletskaya et al, 2019), strategies that enhance and accelerate native extracellular matrix synthesis [e.g., hypoxia (Taheem et al, 2019)] and deposition [e.g., macromolecular crowding ] coupled with electrospinning are likely to lead to more biomimetic three-dimensional cartilage equivalents.…”
Section: Critical Analysis and Outlookmentioning
confidence: 99%
“…Advanced validation tests are the most involved tests using living organ culture systems and/or animals. Organ cultures can characterize healing potential, degradation and mechanical behaviors of repair strategies using human IVDs and/or large animal IVDs (reducing the need or number of whole animals required) but have limits since they lack the immune system of a live animal. Large animal models are important for advanced validation tests since measurements can include assessments of in vivo healing, biocompatibility, biomechanical restoration and in some cases behavioral measurements predictive of painful responses …”
Section: The Importance Of Mechanical Compatibilitymentioning
confidence: 99%